Cost of wound dressing: Implication for enrollment into the National Health Insurance scheme, Nigeria - Kolawole D. Ogundeji; Patrone R. Risenga; Gloria Thupayagale-Tshweneagae (AOSIS, 2023)
Background: Enrollment into the National Health Insurance scheme (NHIS) still poses a challenge in Nigeria despite the established Group, Individual and Family Social Health Insurance Programme (GIFSHIP) during the coronavirus disease 2019 (COVID-19) pandemic. Objectives: This study examined the direct cost of wound dressing and enrollment into the health insurance scheme among hospitalised patients. Method: A descriptive cross-sectional research design was utilised to investigate the cost of wound dressing and enrollment into health insurance scheme among hospitalised patients in three selected hospitals of South-West Nigeria. The study was conducted from March 2021 to June 2021, and 190 patients were recruited via an interviewer-administered questionnaire. Ethical approvals were obtained from the hospitals while COVID-19 preventive protocols and ethical principles of autonomy, confidentiality and non-maleficence were observed. Results: Majority of the respondents (91%) were not on any healthcare insurance scheme, only 4.2% were enrolled in NHIS while over 70% could not personally pay for their wound dressing. The minimum average cost of wound dressing materials per week and per acute care episode was ₦10 000.00 (Nigerian naira) and ₦50 000.00, respectively, while the minimum average cost for hospitalisation per week and per acute care episode was ₦18 000.00 and ₦130 000.00, respectively, ($1.00 equaled ₦600.00, June 2022). Conclusion: A lack of health insurance coverage is a precursor of 'out of pocket' payment. A political will is required to scale up enrollment of the indigenous population into the NHIS in Nigeria. Contribution: Many hospitalised patients are not enrolled in the NHIS and they are at a higher risk of catastrophic healthcare expenditure.